Algeny: a new word -a new world - Rifkin, Jeremy (England, 1984)
In this daring and far-reaching critique Jeremy Rifkin warns of the clear dangers inherent in the new science of genetic engi neering. Offering first a challenging reevaluation of Darwin ism, Mr. Rifkin then goes on to examine critically the way we view our relationship to nature. With the advances of science, a new world view is emerging, based on the notion that nature can be altered to suit humanity's whims. The implications philosophical, moral, and social-are frightening; it is impera tive that we confront the assumptions of biotechnology now, before life on our planet is irreversibly altered.
Keywords: Social Change